Current Status of Cell-Based Therapies for COVID-19: Evidence From Mesenchymal Stromal Cells in Sepsis and ARDS - Xu, Zhiheng; Huang, Yongbo; Zhou, Jianmeng; Deng, Xiumei; He, Weiqun; Liu, Xiaoqing; Li, Yimin; Zhong, Nanshan; Sang, Ling (Frontiers in Immunology, 2021)
The severe respiratory consequences of the coronavirus disease 2019 (COVID-19) pandemic have prompted the urgent need for novel therapies. Cell-based therapies, primarily using mesenchymal stromal cells (MSCs), have demonstrated safety and potential efficacy in the treatment of critical illness, particularly sepsis and acute respiratory distress syndrome (ARDS). However, there are limited preclinical data for MSCs in COVID-19. Recent studies have shown that MSCs could decrease inflammation, improve lung permeability, enhance microbe and alveolar fluid clearance, and promote lung epithelial and endothelial repair. In addition, MSC-based therapy has shown promising effects in preclinical studies and phase 1 clinical trials in sepsis and ARDS. Here, we review recent advances related to MSC-based therapy in the context of sepsis and ARDS and evaluate the potential value of MSCs as a therapeutic strategy for COVID-19.